2013
DOI: 10.1111/boj.12115
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of thePetunia integrifoliacomplex in southern Brazil

Abstract: In this study, we evaluated the genetic diversity of the Petunia integrifolia species group using a phylogeographical approach, and attempted to understand better its diversification and taxonomy. Plants from five morphological groups were collected, covering a large part of the geographical distribution of most of the species. Two major clades were found in the phylogenetic tree, and an additional lineage, corresponding to P. inflata, was found in the haplotype network obtained for plastid markers. All three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
22
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 80 publications
(86 reference statements)
7
22
0
1
Order By: Relevance
“…Similarly, phylogeographic structure (inland and coastline) were reported in the orchid Epidendrum fulgens (Pinheiro & Cozzolino, ; Pinheiro et al., ), and Eugenia uniflora (Turchetto‐Zolet et al., ), highlighting the importance of common historical processes shaping the distribution of several southern Brazilian taxa. A similar movement of populations from western (inland region), and recent colonisation of the coastal plain, was suggested for Calibrachoa heterophylla and the Petunia integrifolia species complex in Solanaceae (Longo, Lorenz‐Lemke, Mäder, Bonatto, & Freitas, ; Mäder, Fregonezi, Lorenz‐Lemke, Bonatto, & Freitas, ). Recently, palaeoclimatic models suggest expansion of forest and forest‐adapted taxa due to opportunities of suitable climatic conditions onto the emerged continental shelf in the LGM in eastern Brazil (Leite et al., ).…”
Section: Discussionsupporting
confidence: 53%
“…Similarly, phylogeographic structure (inland and coastline) were reported in the orchid Epidendrum fulgens (Pinheiro & Cozzolino, ; Pinheiro et al., ), and Eugenia uniflora (Turchetto‐Zolet et al., ), highlighting the importance of common historical processes shaping the distribution of several southern Brazilian taxa. A similar movement of populations from western (inland region), and recent colonisation of the coastal plain, was suggested for Calibrachoa heterophylla and the Petunia integrifolia species complex in Solanaceae (Longo, Lorenz‐Lemke, Mäder, Bonatto, & Freitas, ; Mäder, Fregonezi, Lorenz‐Lemke, Bonatto, & Freitas, ). Recently, palaeoclimatic models suggest expansion of forest and forest‐adapted taxa due to opportunities of suitable climatic conditions onto the emerged continental shelf in the LGM in eastern Brazil (Leite et al., ).…”
Section: Discussionsupporting
confidence: 53%
“…The distribution of L. discrepans and L. pampicola are divided by a central gap suggesting the division of inland western and eastern clusters, as well as a costal cluster in LGM. This structure was also observed in this area for plants endemic to the Southern Grasslands (Pinheiro et al 2011; Longo et al 2014; Silva et al 2018). The species could have dispersed through the “Portal de Torres” (Rambo 1950), a migratory route from the coastal Atlantic forest to the inland grasslands (Pinheiro et al 2011; Barros et al 2018; Silva et al 2018).…”
Section: Discussionsupporting
confidence: 67%
“…integrifolia under the latter taxa, justifying this choice with the association of several characteristics to the different environments where these plants grow. Previous evolutionary approaches (Longo et al , 2014; Reck-Kortmann et al , 2014; Ramos-Fregonezi et al , 2015) have supported the suggestions of Stehmann and Bohs (2007) and Stehmann et al (2009), but the genetic variation found in WOX genes reinforces the proposition of Ando et al (2005a,b), this indicating the need for more studies including these different morphologies.…”
Section: Discussionmentioning
confidence: 62%